2008
DOI: 10.1002/nau.20603
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of dynamometric passive properties of the pelvic floor muscles in postmenopausal women with stress urinary incontinence

Abstract: This new approach for assessing PFM passive properties showed enough reliability for highly recommending its inclusion in the PFM assessment of SUI postmenopausal women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
1
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 23 publications
2
43
1
1
Order By: Relevance
“…While we did not find an effect of task familiarization on passive PFM resistance across sessions, as with our own previous research and that of Morin et al, within sessions we found that resistance to passive stretch applied by the dynamometer, was significantly lower in subsequent repetitions than it was in the initial trial (see Table caption). This finding is important to protocol development when evaluating the stiffness or resistance to passive stretching of the PFMs using intravaginal dynamometry.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…While we did not find an effect of task familiarization on passive PFM resistance across sessions, as with our own previous research and that of Morin et al, within sessions we found that resistance to passive stretch applied by the dynamometer, was significantly lower in subsequent repetitions than it was in the initial trial (see Table caption). This finding is important to protocol development when evaluating the stiffness or resistance to passive stretching of the PFMs using intravaginal dynamometry.…”
Section: Discussionsupporting
confidence: 89%
“…Dysfunction of the mechanical properties of the female pelvic floor muscles (PFMs) is thought to contribute to a wide array of urogynecological disorders known to impair quality of life such as urinary incontinence, pelvic organ prolapse, and dyspareunia . Intravaginal dynamometry is recognized as an optimal tool to quantify active and passive pelvic floor tissue properties . Relative measures of PFM force generating capacity acquired by intravaginal dynamometry have demonstrated excellent reliability and correlate strongly with manual measures of PFM strength, the current standard for clinical assessment of the female PFMs.…”
Section: Introductionmentioning
confidence: 99%
“…Pain intensity (NRS) a [34] Average pain intensity reported during sexual intercourse Dynamometry [47], [48], [49], [50], [51], [52], [53] and [54] PFM function Several secondary outcomes are assessed in this study, in line with the IMMPACT consensus recommending a multi-facetted evaluation of pain, and also an evaluation of the impact of pain on function [34]. For each outcome we have selected measure instruments that have excellent validity, reliability and responsiveness to change.…”
Section: Primary Outcome Measurementioning
confidence: 99%
“…Using this validated and reliable methodology [44], [45] and [46], several parameters are evaluated at rest and during PFM contraction: levator hiatus area and diameter, bladder neck positioning and displacement as well as levator plate and anorectal angles. An intravaginal dynamometric speculum, developed by our team to evaluate PFM function [47], [48], [49] and [50], is also used in this trial. This instrument has been widely assessed for its psychometric properties including its reliability, validity and responsiveness [49], [50], [51], [52], [53] and [54].…”
Section: Primary Outcome Measurementioning
confidence: 99%
See 1 more Smart Citation